2011
DOI: 10.1155/2011/827969
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Moisture Sensor Using a Microstrip Antenna

Abstract: A wireless moisture sensor has been developed on the basis of the backscatter characteristic of the microstrip antenna, which works in the far field without a battery. This study aims to develop a wireless sensor with a long communication distance and to apply the wireless applications, such as monitoring the moisture in the wrapped products and surface adsorption of hydrogen peroxide in the biological isolation systems. The dropwise addition of the distilled water on the cleaning tissue is clearly detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Finally, the proposed sensor is compared to other published results in References in terms of F r , measurement error, structure type, and the distance between the sample and the sensor as listed in Table . It is found that the proposed sensor shows the minimum measurement error with a single port network and far away from the sample of 100 mm.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the proposed sensor is compared to other published results in References in terms of F r , measurement error, structure type, and the distance between the sample and the sensor as listed in Table . It is found that the proposed sensor shows the minimum measurement error with a single port network and far away from the sample of 100 mm.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the proposed sensor shows the minimum measurement error with a single port network and far away from the sample of 100 mm. However, the proposed sensor in Reference may show good sensing ability at 500 mm, but the structure is based on two‐port network that adds more complexity in the design due to the back scattering process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations